Legnicka Specjalna Strefa Ekonomiczna - bilans efektów - Golonka, Tadeusz Piotr (Legnicka Special Economic Zone - Balance of Effects, 2007)
Special Economic Zone (SEZ) from definition is known as an economic instrument to attract boft capital and investors and to create of new jobs and also compensate disproportion in development of regions in the country. One of fourteen SEZ functioning currently in Poland is established in 1997 Legnicka Special Economic Zone (LSEZ). Making an alternative for monoculture of the copper industry with task to develop existing technical infrastructure and lands after the withdrawal of Soviet Army. The effects of functioning of LSEZ measured by number of new jobs, the scale of investment expenditures and expenses, extent of development lands are positive examples, of realization of regional politics and regional aid.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 184-196